Improving Organizational Citizenship Behavior Through Strengthening Organizational Climate and Job Satisfaction - Nancy Yusnita; Widodo Sunaryo; Falentina Falentina (Universitas Pakuan, 2022)
Many researches of Organizational Citizenship Behavior (OCB) had generated findings that OCB considered to be one of the main ways to increase the effectiveness of organizations. The objective of this study is to examine factors that have relationship with OCB namely organizational climate and job satisfaction. This study conducted among employees at Kantor Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) in Jakarta, Indonesia. The sample for the study consisted of 125 employees derived randomly from its population. The study mainly utilized quantitative data (from questionnaires). The regression and correlational analysis used to find out the relationship among variables. The findings revealed that organizational climate had a strong positive and significant relationship with OCB. Similarly, job satisfaction had strong positive and significant relationship with OCB. Both organizational climate and job satisfaction simultaneously had strong positive and significant relationship with OCB. Further analysis conducted to find out which dimensions of those variables that had dominant influenced toward OCB. Based on those findings, this study proposed some recommendations toward BKKBN Office to strengthening indicators of Organizational Climate and Job Satisfaction that have high coefficient of correlation with OCB. Improving employees’ OCB can be predicted increasing the BKKBN organizational effectiveness.